2010
DOI: 10.1111/j.1365-2222.2009.03435.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in allergy trends between East and West Germany and possible explanations

Abstract: Hayfever and sensitization against pollen were the most sensitive allergic manifestations to changes experienced specifically in East Germany. Influences of lifestyle (single-room heating, living as a single child) were important in explaining different trend developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
3
28
1
4
Order By: Relevance
“…Ein unabhängiger Einfluss jedoch zeigte sich schon nicht mehr in den Daten der KiGGS-Basiserhebung [29], wofür unterschiedliche Entwicklungen in Lebensstil und Umweltfaktoren in Ost und West als Gründe angeführt werden [30].…”
unclassified
“…Ein unabhängiger Einfluss jedoch zeigte sich schon nicht mehr in den Daten der KiGGS-Basiserhebung [29], wofür unterschiedliche Entwicklungen in Lebensstil und Umweltfaktoren in Ost und West als Gründe angeführt werden [30].…”
unclassified
“…After the German reunification in 1989, several studies conducted in the early 1990s showed a higher prevalence of allergic diseases such as asthma and hay fever in adults and children [11,12,13] in West Germany (former Federal Republic of Germany) compared to East Germany (former German Democratic Republic). However, total serum IgE levels were found to be higher in East German individuals [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since pollinosis is difficult to cure (Okubo et al 2011), we regarded diagnosis over time as approximating its prevalence before moving. Fourth, areas classified as high pollen areas in this study tended to include developed urban areas and allergic diseases are known to be affected by factors such as automobile exhaust gas (Hazenkamp-von Arx et al 2011), air pollution (Seaton et al 1994) or western lifestyle (von Mutius et al 1998;Kramer et al 2010), these factors were not analysed in this study and their associations remain unclear. Additional studies are needed to further assess these relationships and possible confounding variables.…”
Section: Limitationsmentioning
confidence: 99%
“…The prevalence of pollinosis differs by patient age (Baba et al 2008;Okamoto et al 2009;Okubo et al 2011) and is influenced by several environmental factors, including sibling number (Strachan 1989), farming (Braun-Fahrlander et al 1999;von Mutius and Vercelli 2010), occupational exposure (Gautrin et al 1994), exposure to automobile exhaust gas (Hazenkamp-von Arx et al 2011), air pollution (Seaton et al 1994), and western life-style (von Mutius et al 1998;Kramer et al 2010). Furthermore, the prevalence of pollinosis is affected by geographic environment (Smith 1971;Strachan et al 1997;Austin et al 1999).…”
Section: Introductionmentioning
confidence: 99%